Genetic pleiotropy between mood disorders, metabolic, and endocrine traits in a multigenerational pedigree. Issue 1 (December 2018) - Kember, Rachel; Hou, Liping; Ji, Xiao; Andersen, Lars; Ghorai, Arpita; Estrella, Lisa; Almasy, Laura; McMahon, Francis; Brown, Christopher; Bućan, Maja
Abstract Bipolar disorder (BD) is a mental disorder characterized by alternating periods of depression and mania. Individuals with BD have higher levels of early mortality than the general population, and a substantial proportion of this is due to increased risk for comorbid diseases. To identify the molecular events that underlie BD and related medical comorbidities, we generated imputed whole-genome sequence data using a population-specific reference panel for an extended multigenerational Old Order Amish pedigree (n  = 394), segregating BD and related disorders. First, we investigated all putative disease-causing variants at known Mendelian disease loci present in this pedigree. Second, we performed genomic profiling using polygenic risk scores (PRS) to establish each individual's risk for several complex diseases. We identified a set of Mendelian variants that co-occur in individuals with BD more frequently than their unaffected family members, including the R3527Q mutation inAPOB associated with hypercholesterolemia. Using PRS, we demonstrated that BD individuals from this pedigree were enriched for the same common risk alleles for BD as the general population (β = 0.416, p  = 6 × 10−4 ). Furthermore, we find evidence for a common genetic etiology between BD risk and polygenic risk for clinical autoimmune thyroid disease (p  = 1 × 10−4 ), diabetes (p  = 1 × 10−3 ), and lipid traits such as triglyceride levels (p  = 3 × 10−4 ) in the pedigree. We identify genomic regions that contribute to the differences between BD individuals and unaffected family members by calculating local genetic risk for independent LD blocks. Our findings provide evidence for the extensive genetic pleiotropy that can drive epidemiological findings of comorbidities between diseases and other complex traits.